Interventions for preventing and treating incontinence‐associated dermatitis in adults - Beeckman, Dimitri (Cochrane Database Syst Rev, 2016)
BACKGROUND: Incontinence‐associated dermatitis (IAD) is one of the most common skin problems in adults who are incontinent for urine, stool, or both. In practice, products and procedures are the same for both prevention and treatment of IAD. OBJECTIVES: The objective of this review was to assess the effectiveness of various products and procedures to prevent  and treat incontinence‐associated dermatitis in adults. SEARCH METHODS: We searched the Cochrane Incontinence Group Specialised Trials Register, which contains trials identified from the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, MEDLINE In‐Process, MEDLINE Epub Ahead of Print, CINAHL, ClinicalTrials.gov, WHO ICTRP and handsearching of journals and conference proceedings (searched 28 September 2016). Additionally we searched other electronic databases: CENTRAL(2015, Issue 4), MEDLINE (January 1946 to May Week 3 2015), MEDLINE In‐Process (inception to 26 May 2015), CINAHL(December 1981 to 28 May 2015), Web of Science (WoS; inception to 28 May 2015) and handsearched conference proceedings (to June 2015) and the reference lists of relevant articles, and contacted authors and experts in the field. SELECTION CRITERIA: We selected randomised controlled trials (RCTs) and quasi‐RCTs, performed in any healthcare setting, with included participants over 18 years of age, with or without IAD. We included trials comparing the (cost) effectiveness of topical skin care products such as skin cleansers, moisturisers, and skin protectants of different compositions and skin care procedures aiming to prevent and treat IAD. DATA COLLECTION AND ANALYSIS: Two review authors independently screened titles, abstracts and full‐texts, extracted data, and assessed the risk of bias of the included trials. MAIN RESULTS: We included 13 trials with 1316 participants in a qualitative synthesis. Participants were incontinent for urine, stool, or both, and were residents in a nursing home or were hospitalised. Eleven trials had a small sample size and short follow‐up periods. .The overall risk of bias in the included studies was high. The data were not suitable for meta‐analysis due to heterogeneity in participant population, skin care products, skin care procedures, outcomes, and measurement tools. Nine trials compared different topical skin care products, including a combination of products. Two trials tested a structured skin care procedure. One trial compared topical skin care products alongside frequencies of application. One trial compared frequencies of application of topical skin care products. We found evidence in two trials, being of low and moderate quality, that soap and water performed poorly in the prevention and treatment of IAD (primary outcomes of this review). The first trial indicated that the use of a skin cleanser might be more effective than the use of soap and water (risk ratio (RR) 0.39, 95% confidence interval (CI) 0.17 to 0.87; low quality evidence). The second trial indicated that a structured skin care procedure, being a washcloth with cleansing, moisturising, and protecting properties, might be more effective than soap and water (RR 0.31, 95% CI 0.12 to 0.79; moderate quality evidence). Findings from the other trials, all being of low to very low quality, suggest that applying a leave‐on product (moisturiser, skin protectant, or a combination) might be more effective than not applying a leave‐on product. No trial reported on the third primary outcome 'number of participants not satisfied with treatment' or on adverse effects. AUTHORS' CONCLUSIONS: Little evidence, of very low to moderate quality, exists on the effects of interventions for preventing and treating IAD in adults. Soap and water performed poorly in the prevention and treatment of IAD. Application of leave‐on products (moisturisers, skin protectants, or a combination) and avoiding soap seems to be more effective than withholding these products. The performance of leave‐on products depends on the combination of ingredients, the overall formulation and the usage (e.g. amount applied). High quality confirmatory trials using standardised, and comparable prevention and treatment regimens in different settings/regions are required. Furthermore, to increase the comparability of trial results, we recommend the development of a core outcome set, including validated measurement tools. The evidence in this review is current up to 28 September 2016.